Application of the "Play and Stay" program in the training of tennis players up to 10 years - Dmytro Krylov; Liudmyla Shesterova (Kharkiv State Academy of Physical Culture, 2017)
Purpose: based on the analysis of literature sources and the experience of coaches, to determine the advantages of using the "Play and Stay" program in the training of young tennis players. Material & Methods: in the course of the study, the following methods were used: analysis and generalization of literary sources, generalization of the pedagogical experience of the trainers work. Result: processing accessible to us literary sources has allowed defining advantages and lacks of application of the program "Play and Stay" in preparation of tennis players up to 10 years. Conclusion: it is determined that the program "Play and Stay" is necessary for the training of tennis players up to 10 years, but when they go to standard balls there is a distortion of technical elements that requires a certain correction.